Effectiveness of an instructional module regarding first-aid of pediatric emergencies on knowledge among mothers of 1-6 years children - Arti, Km; Kumari, Rina; Koonwar, Sciddhartha; Charan, Anugrah (International Journal of Contemporary Pediatrics, 2020)
Background: The first aid is given to preserve and protect life, prevent further injury or deterioration of the victim, and help to promote recovery. The objectives of the study were to assess the pre- test knowledge scores regarding first aid of pediatric emergencies among mothers of 1-6 years children, to evaluate the effectiveness of an instructional module regarding first aid of pediatric emergencies on knowledge among mothers of 1-6 years children, to find out the association between the post-test knowledge scores of mothers with their demographic variables. Methods: Quasi-experimental with one group pre-test post-test design was used for 48 mothers at pediatric medical ward, surgery ward and trauma emergency KGMU, Lucknow and purposive sampling technique was used. Self-structured knowledge questionnaires on first aid of pediatric emergencies were used. Based on the objectives and the hypotheses the data were analyzed by using various statistical tests. Results: The result reveals that the overall score was 13.17 in pre-test and 20.13 in post- test after distribution of Instructional module to mothers 22 (45.83%) had good knowledge and 26 (54.17%) had average knowledge regarding first aid of selected conditions of pediatric emergencies. Paired ‘t’ test showed that there was a significant improvement between pre-test and post-test scores with a 't' value of -24.639, p<0.05. Conclusions: The study findings revealed that the Instructional module regarding first aid of Pediatric Emergencies was effective in improving knowledge of mothers of 1-6 years children.